ANALISIS SIKAP MULTIATRIBUT FISHBEIN TERHADAP BUNGA KRISAN PADA PT KEBUN CIPUTRI MOLEK CIANJUR - Safira Fathin; Whilda Marline (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2020)
Chrysanthemum is one of cut flowers which are significantly preferred by consumer. The chrysanthemum products increase continually year by year and in 2018 productivity of the plant was up to 488,18 milion stems. The increasing of the products was also affected by altering consumer preference to the products resulted from farmers and growers. To know the changing of market and consumer preference on chrysanthemum products, research on consumer preference on chrysanthemum flowers was carried out. Objective of the research was to know consumer preference on chrysanthemum flowers. The study was conducted from January to April 2020. Data collecting both primary and secondary was carried out by survey method. Respondents were selected purposively, 30 consumers for chrysanthemum in PT Kebun Ciputri Molek. The method of data analysis used in this study is a model of Fishbein’s multi-attribute. The attributes considered most important by respondents were the type of flower attribute, followed by flower color, flower shape, high rigidity, vaselife, size of flower and price. Results of the study, furthermore, can be used as basic of farmers, growers, and breeders in producing the products suitable with market and consumer need.Keywords: Chrysanthemum flowers, consumer preferences, fishbein